The Application of The Problem Based Learning Model to Improve Student Learning Outcomes in Natural Science Lesson in Class IV of SD Negeri Ngrajek 1 - Lenny Aprilitsnaeni (Universitas Sebelas Maret, 2020)
The science learning process carried out by the teacher is still conventional which tends to make students feel bored and does not provide opportunities for students to be active in learning so that there are still many students who have difficulty following the learning process which results in low student learning outcomes. This problem is also experienced by students at SD Negeri Ngrajek 1. The purpose of this study is to improve student learning outcomes through the Problem Based Learning learning model for fourth grade students at SD Negeri Ngrajek 1. The research form is Classroom Action Research (CAR). Based on the percentage of student learning outcomes, the average value in each cycle can be obtained, namely in the first cycle there was an increase in the average value of 8.75, namely the initial average value of 66.25 increased to 75. Classical student learning outcomes are still classified as moderate. with an average acquisition of 79 in the 70-79 interval in the medium category. In the second cycle the average score of students increased by 12.5, which was originally an average of 66.5 students in the second cycle the average value was 79 in the medium category. In cycle III the average score of students also increased by 14.5, which was originally 66.5 students on average in cycle III the average value was 81. Classical student learning outcomes were in the interval 80-89 in the high category. This means that learning through the Problem Based Learning method can improve the learning outcomes of fourth grade students at SD Negeri Ngrajek 1.